From Review to Practice: Digital Integration of BIM and GIS for Multi-Hazard Vulnerability Analysis and Climate Resilience of Buildings - Steffen Neuner; Munschauer, C.; Braun, C.; Fekete, A.; Leopold, U.; Pinheiro, P.; Stellacci, S.; Yilmaz, D.; Ferreira da Silva, C. (International Conference on Resilient Systems, 2026)
The contribution outlines a workflow that includes a scientific review and the development of an exposure and vulnerability database, integrating Building Information Models (BIM) and Geographic Information Systems (GIS). The database is aligned with the emerging concerns in the European Union regarding the future-proofing of buildings in the context of climate change and increasing natural hazard frequency and intensity. The results of a scientific review provide the baseline for vulnerability assessments of buildings, leveraging a threedimensional geodatabase that incorporates BIM. The objective is to facilitate the ability of homeowners to make informed decisions regarding retrofitting strategies and resilience measures.